Pitfalls in a Sonographic Diagnosis of Liver Abscess in Children - Chun-Chun Chuang; Shu-Fen Wu; An-Chyi Chen; Ming-Feng Tsai; Ching-Yuang Lin; Walter Chen (Elsevier, 2012)
The purpose of this article is to identify the pitfalls of sonography in the diagnosis of liver abscesses, hematomas, and hepatic tumors, which appear similar and therefore are difficult to differentiate from each other. Methods: Cases were collected at the China Medical University Hospital between January 2008 and January 2010. Liver abscesses were initially diagnosed by sonograph in selected patients who were younger than 18 years. Results: There were 15 patients in whom a liver mass was diagnosed by ultrasound, but 6 of them were excluded from further study because of failure to meet any of the screening criteria. Nine patients with a mean age of 11.3 years (range 5-17 years) were initially suspected to have liver abscesses by ultrasound and were enrolled in the study. These nine patients were identified as follows: five with liver abscess, one with liver hematoma, one with hepatic lymphoma, one with perihepatic abscess, and one with undifferentiated liver sarcoma. Ultrasonography alone was sufficient for diagnosis in five patients. Four patients required abdominal CT scanning to confirm final diagnosis. Conclusion: Different liver lesions may present sonographic images similar to those of liver abscesses. Therefore, it is suggested that patients in whom liver abscesses were diagnosed by ultrasound undergo further evaluation if the clinical condition is less likely.